2008
DOI: 10.1210/jc.2008-0375
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Free Growth Hormone

Abstract: It is possible to measure free GH in human serum. Free GH correlated positively with total GH and inversely with GHBP. Measurement of free GH may be a helpful future tool in the management of GH disorders and in studies of GH-GHBP interrelationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Frystyk et al (16) speculated that GHBP may regulate GH bioactivity via an unknown mechanism. Therefore, we examined correlations between bGH, iGH, and GHBP over the course of the exercise protocol to explore whether different feedback mechanisms may play a role in differences in GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Frystyk et al (16) speculated that GHBP may regulate GH bioactivity via an unknown mechanism. Therefore, we examined correlations between bGH, iGH, and GHBP over the course of the exercise protocol to explore whether different feedback mechanisms may play a role in differences in GH secretion.…”
Section: Discussionmentioning
confidence: 99%
“…GH not associated with GHBP (identical to the truncated, extracellular domain of the GHR), were determined by a novel, validated in-house ultrafiltration assay that allows separation of free from bound GH at approached in vivo-like conditions. The separation procedure was performed as described recently (18). The obtained ultrafiltrates were assayed for GH using the GH Delfia, performed according to the instructions by the manufacturer, with overall intra-and inter-assay CV values averaging 7 and 11% respectively, i.e.…”
Section: Assaysmentioning
confidence: 99%
“…When estimating free GH using ultrafiltration by centrifugation to retain GHBP, Frystyk et al (29) found a positive correlation between total and free GH and an inverse relation between free GH and GHBP. In our study population, GHBP levels remained unchanged whereas GH increased significantly.…”
Section: Discussionmentioning
confidence: 99%